2021
DOI: 10.1002/acr2.11233
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effect of Electronic Medical Record Modifications and Lean Six Sigma Methodology on Rheumatoid Arthritis Disease Activity Measurement and Treat‐to‐Target Outcomes

Abstract: Objective Rheumatoid arthritis (RA) disease activity assessment is critical for treatment decisions and treat to target (T2T) outcomes. Utilization of the electronic medical record (EMR) and techniques to improve the routine capture of disease activity measures in clinical practice are not well described. We leveraged a Lean Six Sigma (LSS) approach, a data‐driven five‐step process improvement and problem‐solving methodology, coupled with EMR modifications to evaluate improvement in disease activity documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…19 Our study thus extends the previous literature demonstrating the efficacy of educational programs and ICU bundles in increasing awareness of and preparation to assess and treat delirium. 20 We hope that the significant improvement in delirium assessment compliance we observed in this QI study will lead to better detection and management of pediatric delirium. Future work should assess the clinical implications of this project—specifically, how increased accuracy in delirium screening may lead to more timely diagnosis and treatment for patients with delirium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…19 Our study thus extends the previous literature demonstrating the efficacy of educational programs and ICU bundles in increasing awareness of and preparation to assess and treat delirium. 20 We hope that the significant improvement in delirium assessment compliance we observed in this QI study will lead to better detection and management of pediatric delirium. Future work should assess the clinical implications of this project—specifically, how increased accuracy in delirium screening may lead to more timely diagnosis and treatment for patients with delirium.…”
Section: Discussionmentioning
confidence: 82%
“…The significant role of EMR-based interventions in quality improvement in hospital settings in general, and ICU in particular, has been widely demonstrated. 16 18 This quality improvement project contributes to the existing literature by showing that one EMR-related intervention, introducing protocol flowsheets, improves compliance with delirium assessments. Future studies might focus on additional interventions that introduce newer automated systems into EMRs to aid healthcare professionals in conducting and documenting easily and efficiently.…”
Section: Discussionmentioning
confidence: 97%
“…Other research has demonstrated the effectiveness of data feedback both through audit-and-feedback mechanisms and through specific use of tailored electronic health record tools [ 30 , 31 , 32 , 33 ]. Notably, the combination of health record tools and systems redesign approaches have worked in other clinical areas [ 34 ]. However, none of these approaches are effective if they are not acceptable to clinicians and utilized in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Six Sigma is a form of quality improvement towards the target of 3.4 defects per million opportunities (DPMO) for each product, both goods and services reduce the number of defects. Six Sigma can also be defined as a business process improvement method that aims to find and reduce the factors that cause defects, reduce cycle times and production costs, increase productivity, meet customer needs, achieve optimal machine utility, and get better results [9]. Both in terms of production and service.…”
Section: Literature Reviewmentioning
confidence: 99%